Chapter 10 Imagining a Cosmopolitized Europe. From the Study of the 'New' to the Discovery of the 'Unexpected - Selchow, Sabine (Universitätsverlag Göttingen, 2015)
If we look at the contemporary academic discourse of political studies in gen- eral and the scholarship on international relations in particular, we notice that many analysts start on the basis that there is something 'new' about the world: that it is a "brave new world"1 we are living in, that we are facing 'new' challenges and problems and threats, and that 'new' solutions are needed. Starting on this premise, much of the scholarship in political studies and international relations is then about the study of this 'new' world and the search for 'new' solutions that could address and deal with the perceived 'new' challenges we are said to be facing